Terminologišče – kraj, kjer terminolog išče - Žagar Karer, Mojca (Slavia Centralis, 2020)
TERMINOLOGIŠČE – A PLACE TO SEARCH FOR TERMINOLOGY Terminologišče is a website of the Terminological Section of the Fran Ramovš Institute of the Slovenian Language where one can fnd a presentation of the Section and its dictionary projects, a short description of the methodology used for making terminological dictionaries, and a selection of terminological theory. Moreover, the website hosts a search engine where one can browse 10 explanatory terminological dictionaries that were published in printed form the year 2000 onward. It also offers terminological advice to experts on terminological issues. In this article we present the design and construction of Terminologišče.
Keywords: terminology; terminological dictionary; advising on terminology; Terminologišče